A novel tool for suspension culture of human induced pluripotent stem cells: Lysophospholipids as a cell aggregation regulator - Ibuki, Masato (Regen Ther, 2019)
Suspension culture for the increase in human induced pluripotent stem cells (hiPSCs) has been one of the major challenges. Previously, we reported that albumin-associated lipids prevented aggregation of hiPSCs, whereas, lipids responsible for this function were unclear. Here, by using cell aggregation assay, we investigated principal lipids regulated aggregation size of hiPSCs. As a result, lysophosphatidic acid (LPA) and Sphingosine-1-phosphate (S1P), known as lysophospholipids acting as a signaling molecule, were identified. These lipids regulated the aggregation size in a dose-dependent manner. Aggregates formed with these lipids kept the high-expression rates of pluripotent marker genes and had the abilities of proliferation. These studies demonstrated that LPA and S1P were useful for suspension culture for hiPSCs without affecting the growth ability and pluripotency of hiPSCs. This knowledge will lead to the development of a simple and robust method for the mass culture of hiPSCs.